Hospital nurses' individual priorities, internal psychological states and work motivation. (4th August 2014) - Toode, K.; Routasalo, P.; Helminen, M.; Suominen, T.
<x xml:space="preserve">Abstract</x> Aim This study looks to describe the relationships between hospital nurses' individual priorities, internal psychological states and their work motivation. Background Connections between hospital nurses' work‐related needs, values and work motivation are essential for providing safe and high quality health care. However, there is insufficient empirical knowledge concerning these connections for the practice development. Methods A cross‐sectional empirical research study was undertaken. A total of 201 registered nurses from all types of Estonian hospitals filled out an electronic self‐reported questionnaire. Descriptive statistics, Mann–Whitney, Kruskal–Wallis and Spearman's correlation were used for data analysis. Results In individual priorities, higher order needs strength were negatively correlated with age and duration of service. Regarding nurses' internal psychological states, central hospital nurses had less sense of meaningfulness of work. Nurses' individual priorities (i.e. their higher order needs strength and shared values with the organization) correlated with their work motivation. Their internal psychological states (i.e. their experienced meaningfulness of work, experienced responsibility for work outcomes and their knowledge of results) correlated with intrinsic work motivation. Discussion Nurses who prioritize their higher order needs are more motivated to work. The more their own values are compatible with those of the organization, the more intrinsically motivated they are likely to be. Conclusion Nurses' individual achievements, autonomy and training are key factors which influence their motivation to work. Limitations The small sample size and low response rate of the study limit the direct transferability of the findings to the wider nurse population, so further research is needed. Implications for Nursing and Health Policy This study highlights the need and importance to support nurses' professional development and self‐determination, in order to develop and retain motivated nurses. It also indicates a need to value both nurses and nursing in healthcare policy and management.